Recognition and Real-Time Detection of Blinking Eyes on Electroencephalographic Signals Using Wavelet Transform - Salinas-Silva, R; Schachter-Cisternas, E (2012)
In this paper we study the detection of a specific pattern associated with the blinking of an eye in real time using electroencephalogram (EEG) signals of a single channel. This paper takes into account the theoretical and practical principles enabling the design and implementation of a system for real-time detection of time location, regardless of scale and multiple incidences. By using wavelet transform it permits us the fulfillment of our objective. The multiple detection and real-time operation is achieved by working with a pop-up window giving the projection of an ongoing analysis of the signal sampled by the EEG. © 2012 Springer-Verlag.